2014
DOI: 10.4161/hv.29743
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of the immunogenicity and safety of Japanese Encephalitis Chimeric Virus Vaccine (JE-CV) in comparison with SA14-14-2 Vaccine in children in the Republic of Korea

Abstract: A new live attenuated Japanese encephalitis chimeric virus vaccine (JE-CV) has been developed based on innovative technology to give protection against JE with an improved immunogenicity and safety profile. In this phase 3, observer-blind study, 274 children aged 12−24 months were randomized 1:1 to receive one dose of JE-CV (Group JE-CV) or the SA14–14–2 vaccine currently used to vaccinate against JE in the Republic of Korea (Group SA14–14–2). JE neutralizing antibody titers were assessed using PRNT50 before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
5
27
1
Order By: Relevance
“…This evidence has strengthened the existing knowledge about the safety of this vaccine obtained via other study designs [5-8, 10-13, 23]. Our study further support the previously published evidence of that the majority AEFI for LJEV occur during the first 14 days following immunisation [8,23]. In addition, this study documents safety of LJEV when it is given at the age of 9 months.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This evidence has strengthened the existing knowledge about the safety of this vaccine obtained via other study designs [5-8, 10-13, 23]. Our study further support the previously published evidence of that the majority AEFI for LJEV occur during the first 14 days following immunisation [8,23]. In addition, this study documents safety of LJEV when it is given at the age of 9 months.…”
Section: Discussionsupporting
confidence: 80%
“…Since previous studies have reported that majority of vaccine related AEs occur within 14 days of LJEV administration, we analysed the AEs which occurred in 0-14 days separately from those occurred in the next 15-45 days [8,23].…”
Section: Resultsmentioning
confidence: 99%
“…120 In Thai and Philippine children aged 12-24 months, the vaccine could produce 96% SPR after a single dose, 22123 and boost NAb responses elicited earlier by MBDI vaccine with SCR of >90% and SPR of 100% in 2-5-year-old children, 31 as well as 2 years following priming with JE-CV. 124 In a head-to-head comparison of JE-CV and SA14-14-2 LAV vaccines in 12-18-monthold Thai and 12-24-month-old South Korean children, SPRs were equivalent to each other, whereas 28-day GMTs were higher, albeit not statistically significant, with JE-CV than with SA14-14-2 LAV vaccine., 125,126 JE-CV has also been shown to elicit anamnestic responses and significantly increase GMTs in 1-to-5-year-old Thai children who had been vaccinated 9-13 or 12-24 months earlier with the SA-14-14-2 LAV vaccine; 127,128 incidentally, the responses were slightly, but not significantly higher when the booster with JE-CV was later than earlier.…”
Section: Genetically Engineered Vaccinesmentioning
confidence: 95%
“…An overview of the 16 studies that met the inclusion criteria are summarized in Table 1. The studies, which were conducted between 1995 and 2015 in various Asian countries, consist of 7 prospective cohort studies, 8,24-29 3 PMS studies, [21][22][23] 2 openlabel, nonrandomized single arm trials, 30,31 one prospective randomized trial with a control group, 32 2 observer-blind, randomized controlled trials (RCT) comparing LAJEV to JE-CV, 33,34 and one 4-arm, double-blind RCT assessing lot-to-lot consistency of LAJEV. 35…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…8,27,28,31,32 In 2 RCTs, children were randomized 1:1 to receive either LAJEV or JE-CV. 33,34 One study that administered a single dose of LAJEV required children to have previously received the inactivated mouse brain-derived vaccine. 30 All studies, except one 29 which did not clearly specify, excluded children from vaccination if they had visible signs of sickness (e.g., a fever, cough or cold); however, the stringency of the exclusion criteria applied varied by study.…”
Section: Study Subjects and Vaccinationmentioning
confidence: 99%